1987
DOI: 10.1111/j.1365-2052.1987.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic plasma postalbumins of some domestic animals (pig PO2, horse Xk and dog Pa proteins) identified as homologous to human plasma α1B‐glycoprotein

Abstract: Pig, horse and dog plasma proteins, separated by horizontal polyacrylamide gel electrophoresis (pH 9.0) and electrophoretically transferred to nitrocellulose membranes, were tested for cross-reaction with antiserum to human plasma alB-glycoprotein (alB). The results showed that one previously reported polymorphic plasma postalbumin in each of these species (pig P02, horse Xk and dog Pa protein) was homologous to human plasma alB. In the light of the previously known genetic linkages in these species, this impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…In horse, the syntenic group on chromosome 10 now comprises the CRC locus and the three loci of linkage group IV viz. malic enzyme (MEl), AlBG, and GPI (Weitkamp et al 1982;Andersson et al 1983;Juneja et al 1987). Further, the results of the present study indicate that the CRC gene localizes on the same band regions of chromosome 18 in cattle and chromosome 10 in horse, where the GPI gene has earlier been mapped.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In horse, the syntenic group on chromosome 10 now comprises the CRC locus and the three loci of linkage group IV viz. malic enzyme (MEl), AlBG, and GPI (Weitkamp et al 1982;Andersson et al 1983;Juneja et al 1987). Further, the results of the present study indicate that the CRC gene localizes on the same band regions of chromosome 18 in cattle and chromosome 10 in horse, where the GPI gene has earlier been mapped.…”
Section: Discussionsupporting
confidence: 61%
“…Whether this conservation extends to other mammalian species, is not yet known. The GPI locus has been mapped to the 10pter region in horse (Harbitz et al 1990a) and previous studies (Anderson et al 1983;Juneja et al 1987) have shown that the GPI and the alpha-l-B-glycoprotein (AlBG) loci are linked. In cattle, the GPI locus has been regionally mapped to chromosome segment 18q22-proximal part of q24 (Chowdhary et al 1991), andWomack et al (1989) found the locus to be syntenic with diaphorase 4 (DIA4).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is the first to document genetic polymorphism of alB in camelid species. a l B polymorphism was reported in human, horse, pig, dog, arctic fox, sheep and rabbit Juneja et al 1987bJuneja et al , 1988Stratil etal. 1987Stratil etal.…”
Section: Discussionmentioning
confidence: 97%
“…(1990) 18 in cattle now comprises the loci for CRC, GPI and DIA4. AlBG (Andersson et al 1983;Juneja et al 1987;Eiberg et al 1989). malic enzyme (MEl), AlBG, and GPI (Weitkamp et al 1982;Andersson et al 1983;Juneja et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…These represent the first formal evidence of conservation (Nadeau 1989). The GPI locus has been mapped to the 10pter region in horse (Harbitz et al 1990a) and previous studies (Anderson et al 1983;Juneja et al 1987) have shown that the GPI and the alpha-l-B-glycoprotein (AlBG) loci are linked. human, pig and mouse (Cavanna et ul.…”
Section: Introductionmentioning
confidence: 99%